A New Horizon in Facial Plastic Surgery: Skin Tissue-Engineering and Stem Cell Therapy—Reality or Dream?. (September 2014) - Keyhan, Seied Omid; Hemmat, Seifollah; Asayesh, Mohammad Ali; Mehriar, Peyman; Khojasteh, Arash
Facial skin replacement after burns or other injuries has proved to be a challenging task in wound healing. The application of laboratory-based tissue-expansion techniques is a potential solution to the problem of surface area cover. Considerable progress has been made in approaches to these techniques, including allograft and autograft skin transplantation to replace skin temporarily or permanently. Methods for handling skin wounds, such as transplantation, tissue engineering, and, more recently, stem cell therapies, have advanced in the past few decades. Issues with these techniques still remain, though. Development of new treatments for facial burn or wound victims is still a problem in cultured skin grafts. Hair follicles, sweat glands, and other features of normal skin are absent in cultured skin. Scientists believe stem cells with unique characteristics, including self-renewal and differentiation potential offer a possible way for reconstructing some structures within a wound. Enhanced understanding of these new approaches may help researchers develop novel therapies to overcome the problems in facial wound healing.